Drug susceptibility of clinical isolates of Mycobacterium avium complex - D. A. Starkova; V. Yu. Zhuravlev; N. S. Solovieva (Туберкулез и болезни лёгких)
The objective: to study drug susceptibility of M. avium and M. intracellulare isolates received from patients with mycobacteriosis residing in the North Western Federal District using the Sensititre SLOMYCO panels.Subjects and Methods. From 2014 to 2020, 192 slow-growing MAC strains (164 – M. avium, 28 – M. intracellulare) obtained from HIV-negative patients with pulmonary mycobacteriosis were studied. Drug susceptibility testing of MAC strains was performed using the Sensititre SLOMYCO panel consisting of 13 antibacterial drugs.Results. Of the 13 antibacterial drugs, clarithromycin was also most effective against both M. avium (67.1%; 110/164) and M. intracellulare (60.7%; 17/28) (p > 0.05). The proportion of M. avium and M. intracellulare strains sensitive to linezolid was high and amounted to 57.3 and 53.5%, as well as to amikacin – 57.3 and 53.5% respectively.Of the four antibacterial drugs of the Sensititre SLOMYCO panel (clarithromycin, moxiﬂoxacin, linezolid, and amikacin), for which critical concentrations (CC) were established, clarithromycin was the most eﬀective against M. avium and M. intracellulare. Antibiotic-resistant M. avium isolates were more frequent in the group of previously treated patients.